2022
DOI: 10.1186/s12884-022-05301-x
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of health facilities to provide safe childbirth in Liberia: a cross-sectional analysis of population surveys, facility censuses and facility birth records

Abstract: Background The provision of quality obstetric care in health facilities is central to reducing maternal mortality, but simply increasing childbirth in facilities not enough, with evidence that many facilities in sub-Saharan Africa do not fulfil even basic requirements for safe childbirth care. There is ongoing debate on whether to recommend a policy of birth in hospitals, where staffing and capacity may be better, over lower level facilities, which are closer to women’s homes and more accessibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…8 However, the CS rate did not reflect that improvement, with 6.1% born via CS in urban areas compared to 3.7% in rural areas, far below the 9%-19% of the ideal population coverage. 8,16,17 Furthermore, in 2019, about 84% of deliveries in Bong County occurred in a health facility, with 81% taking place within RHFs. 13 This study found that the MORES intervention was associated with approximately 1.8 times higher CS rate, indicating that the intervention may be improving the unmet need of CS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 However, the CS rate did not reflect that improvement, with 6.1% born via CS in urban areas compared to 3.7% in rural areas, far below the 9%-19% of the ideal population coverage. 8,16,17 Furthermore, in 2019, about 84% of deliveries in Bong County occurred in a health facility, with 81% taking place within RHFs. 13 This study found that the MORES intervention was associated with approximately 1.8 times higher CS rate, indicating that the intervention may be improving the unmet need of CS.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a study conducted in Rwanda found that longer travel time from RHF to a hospital was significantly associated with adverse neonatal outcome, emphasizing the need for strategies to reduce the transfer delay from health centers to district hospitals 4 . Despite this need, only 40% of RHFs in Liberia were ready to make an emergency referral, defined as having access to a functional ambulance or other vehicle stationed at the facility or access to an ambulance and a functioning telephone, either a landline or a mobile phone 8 . Hence, there is a need for an efficient and effective communication mechanism between RHFs and hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Liberia's facility-based deliveries significantly increased between 2004 and 2017, from 37% to 80% (8). Most of the increase occurred in rural areas, closing the gap between urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted in Rwanda found that longer travel time from RHF to a hospital was significantly associated with adverse neonatal outcome, emphasizing the need for strategies to reduce the transfer delay from health centers to district hospitals (4). Despite this need, only 40% of RHFs in Liberia were ready to make an emergency referral, defined as having access to a functional ambulance or other vehicle stationed at the facility or access to an ambulance and a functioning telephone, either a landline or a mobile phone (8). Hence, there is a great need to implement efficient and effective communication mechanisms between RHFs and hospitals to improve the referral process and ultimately maternal and newborn outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…18,[21][22][23][24] For example, increasing skilled birth attendance does not guarantee a reduction in maternal mortality, as was seen in Liberia and Ethiopia. 25,26 Taken in aggregate, these ndings suggest that structural quality is necessary but not su cient to increase utilization and improve quality.…”
Section: Introductionmentioning
confidence: 98%